(untitled) (Bangladesh Heart Journal, 2023)
Background: Young people who avoid strokes live longer and have more productive lives than their senior counterparts. The prevalence of the main vascular risk factors in atherosclerosis patients rises with age, starting in early middle age, and declines beyond 70–80 years. The majority of studies on young people are small and single-center, which makes generalization challenging. Stroke risk factors differ between men and women, and vascular risk factors are more prevalent in older age groups of young adult stroke patients. Objective: The aim of the study is to find out the association of cardiac risk factors in young patients. Methods: This hospital-based cross-sectional study was carried out in the indoor patients in the Shaheed Suhrawardy Medical College Hospital, Dhaka, from April 2015 to October 2015. Young stroke patients (15-45 years old) admitted to the hospital were used as the study’s sample size. Results: According to this study, the majority of patients (36.0%) were between the ages of 41 and 45. The percentages of patients in the 26–30–year–old, 31–35– year–old, and 36–40–year–old age groups were fairly close to one another (18.0%, 20.0%, and 22.0%, respectively). Just 4.0% of the population was under 25. The majority of the patients (64.0%) suffered from valvular heart disease. In addition, 10.0% had ischemic heart disorders, 16.0% had myocardial infarction, and 8.0% had atrial fibrillation. More over 75.0% of stroke patients also had some type of heart illness, according to the Framingham Heart study risk calculation. Conclusion: Young adults from Bangladesh who suffered an ischemic stroke exhibited a high incidence of known cardiac risk factors, significant sex disparities, and alarmingly rising trends with age in both sexes. Regardless of where a person lives in the nation, preventive actions must be more aggressive and customized to each individual’s specific risk profile. Bangladesh Heart Journal 2023; 38(1): 81-87